2012
DOI: 10.1590/s0004-282x2012000700012
|View full text |Cite
|
Sign up to set email alerts
|

Is magnetic resonance imaging a plausible biomarker for upper motor neuron degeneration in amyotrophic lateral sclerosis/primary lateral sclerosis or merely a useful paraclinical tool to exclude mimic syndromes? A critical review of imaging applicability in clinical routine

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease that affects motor neurons in the cerebral cortex, brainstem, and spinal cord, brain regions in which conventional magnetic resonance imaging is often uninformative. Although the mean time from symptom onset to diagnosis is estimated to be about one year, the current criteria only prescribe magnetic resonance imaging to exclude "ALS mimic syndromes". Extensive application of non-conventional magnetic resonance imaging (MRI) to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…MRS studies have confirmed the finely tuned balancing act between glutamate and GABA in the human brain both biochemically, as the huge majority of GABA is metabolized from glutamate, and functionally, with regard to the strict control of the inhibitory/excitability balance in healthy [6,12]. However, it has been reported that MRS gives a less accurate reflection of glutaminergic actions than GABAergic activity [10,11]. All these contentions led us to hypothesize that GABA MRS may represent an indirect promising tool to evaluate riluzole efficacy with timely detailed description of the dynamics of changes in GABA levels due to druginduced effects on extracellular glutamate uptake.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…MRS studies have confirmed the finely tuned balancing act between glutamate and GABA in the human brain both biochemically, as the huge majority of GABA is metabolized from glutamate, and functionally, with regard to the strict control of the inhibitory/excitability balance in healthy [6,12]. However, it has been reported that MRS gives a less accurate reflection of glutaminergic actions than GABAergic activity [10,11]. All these contentions led us to hypothesize that GABA MRS may represent an indirect promising tool to evaluate riluzole efficacy with timely detailed description of the dynamics of changes in GABA levels due to druginduced effects on extracellular glutamate uptake.…”
mentioning
confidence: 94%
“…Intriguingly, it has been found that riluzole significantly enhances glutamate uptake in a dose-dependent manner increasing the affinity of glutamate for the transporters including EAAC1 [9]. Magnetic Resonance Spectroscopy (MRS) is a powerful methodology that allows to quantify neurotransmitter concentrations in discrete regions of the human brain non-invasively in vivo [4,10]. Over recent years there has been a particular interest in using this technique to detect biologically relevant alterations in GABA concentrations [10,11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A plausible biomarker for upper motor neuron degeneration in ALS is becoming tangible after recent advances in high-throughput MRI techniques, through which one can believe that we are going to the forefront of a breakthrough able to translate research findings into reliable clinical tests that will support the practice of personalized medicine 8,9,10 .…”
mentioning
confidence: 99%
“…Therefore, there is currently great interest in developing biomarkers of cognitive and extra-motor systems damage in ALS. In this regard, new neuroimaging techniques are postulated as potential tools to obtain accurate data and measure early activity in non-motor structures 4 . Diffusion tensor imaging (DTI) is a technique of magnetic resonance imaging (MRI) used to characterize the architecture of the white matter, based on the orientation properties of diffusion of water molecules in the brain 5 .…”
mentioning
confidence: 99%